2022
DOI: 10.1037/tra0000544
|View full text |Cite
|
Sign up to set email alerts
|

Attachment loss and trauma: A descriptive phenomenological analysis of suicidality and depression in veterinarians.

Abstract: Objective: Suicidality and depression are disproportionately prevalent among veterinarians. Researchers for this study sought to explore the lived experiences of veterinarians in order to better identify the factors that contribute to this phenomenon. Method: Using a qualitative descriptive phenomenological approach, small animal veterinarians in the greater Seattle area were interviewed and provided their respective occupational experiences as they related to depression, suicidality, and coping. Results: Anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 32 publications
2
9
0
Order By: Relevance
“…Previous studies in the animal carer populations have supported this proposition with increasing job control and organisational resources associated with reductions in burnout, exhaustion, and psychological distress, along with increases in work engagement (Black et al, 2011;Kimber & Gardner, 2016). Other resources, such as environments supporting processing of emotions and encouraging learning are also regarded as valuable sources of coping by animal care professionals (Waters et al, 2019). These findings support predictions of the SSM, where availability of organisational resources is expected to predict increasing empowerment and outcomes in resilience.…”
Section: Organisational Climatesupporting
confidence: 73%
See 2 more Smart Citations
“…Previous studies in the animal carer populations have supported this proposition with increasing job control and organisational resources associated with reductions in burnout, exhaustion, and psychological distress, along with increases in work engagement (Black et al, 2011;Kimber & Gardner, 2016). Other resources, such as environments supporting processing of emotions and encouraging learning are also regarded as valuable sources of coping by animal care professionals (Waters et al, 2019). These findings support predictions of the SSM, where availability of organisational resources is expected to predict increasing empowerment and outcomes in resilience.…”
Section: Organisational Climatesupporting
confidence: 73%
“…Interactions with human owners of unwell pets is another source of stress, as an owner's grief, unrealistic expectations, anger, refusal to pay or follow best-practice treatment can increase emotional and empathetic burden (Deacon & Brough, 2019;Polachek & Wallace, 2018). Death or illness of an animal in care can be difficult, particularly when a human-animal bond has been formed (LaFollette et al, 2020;Waters et al, 2019). Death may be a result of euthanasia which can be performed for a variety of reasons, such as on compassionate grounds to end suffering (Von Dietze & Gardner, 2014), at completion of laboratory studies (LaFollette et al, 2020), or due to a human client's financial situation or unwillingness to treat (Deacon & Brough, 2019).…”
Section: Costs and Benefits Of Caringmentioning
confidence: 99%
See 1 more Smart Citation
“… 10 Dealing with bereaved clients (ie, animal owners) has been shown to impact the mental health of veterinarians, 11 and attachment loss and trauma can contribute to both depression and suicidality. 12 Preoccupation, self-doubt, conflicting responsibilities (care of animals/human clients/financial demands) and insufficient support were important factors of job stress among veterinarians in a qualitative study. 13 When searching for independent work-related factors associated with suicidal thoughts and behaviour, it is important to control for known individual factors.…”
Section: Introductionmentioning
confidence: 94%
“…It has been suggested that suicidal ideation among veterinarians is linked to the demanding nature of their work 10. Dealing with bereaved clients (ie, animal owners) has been shown to impact the mental health of veterinarians,11 and attachment loss and trauma can contribute to both depression and suicidality 12. Preoccupation, self-doubt, conflicting responsibilities (care of animals/human clients/financial demands) and insufficient support were important factors of job stress among veterinarians in a qualitative study 13.…”
Section: Introductionmentioning
confidence: 99%